Curing of polymeric composites using microwave resin transfer moulding (RTM) - Yusoff, R.; Aroua, M.K.; Nesbitt, A.; Day, R.J. (Journal of Engineering Science and Technology, 2007)
The main objective of this work is to compare the difference between microwave heating and conventional thermal heating in fabricating carbon/epoxy composites. Two types of epoxy resin systems were used as matrices, LY5052-HY5052 and DGEBA-HY917-DY073. All composite samples were fabricated using resin transfer moulding (RTM) technique. The curing of the LY5052-HY5052-carbon and the DGEBA-HY917-DY073-carbon composite systems, were carried out at 100 °C and 120 °C, respectively. Microwave heating showed better temperature control than conventional heating, however, the heating rate of the microwave cured samples were slower than the conventionally cured samples. This was attributed to the lower power (250 W) used when heating with microwaves compared to 2000 W used in conventional heating. Study of thermal characteristics as curing progressed showed that the polymerisation reaction occurred at a faster rate during microwave curing than in conventional curing for both the DGEBA and the LY/HY5052 carbon composite systems. The actual cure cycle was reduced from 60 minutes to 40 minutes when using microwaves for curing DGEBAcarbon composites. As for LY/HY5052-carbon composites, the actual cure cycle was reduced from 3 hours to 40 minutes. Both conventional and microwave heating yielded similar glass transition temperatures (120 °C for DGEBA systems and 130 °C for LY/HY5052 systems). Microwave cured composites had higher void contents than conventionally cured composites (2.2-2.8 and 1.8-2.4 for DGEBA and LY/HY5052 microwave cured composites, respectively, compared to 0.2-0.4 for both DGEBA and LY/HY5052 thermally cured composites). C-scan traces showed that all composites, regardless of methods of curing, had minimal defects.